Digiteka - prispevek k razpravi o "digitalni knjižnici" - Šercar, Tvrtko (Organizacija znanja, 2006)
This article pleads for the term "digitheca" to be used instead of the less suitable term "digital library". It introduces functional and non-functional requirements for the assessment and selection of software in the global software market, which supports the creation, maintenance and preservation of a "digitheca".
Keywords: digitalne knjižnice; računalniška programska oprema